Secondhand smoke exposure at home and respiratory symptoms among primary school children in Kota Bharu, Kelantan - Sharina D.; Zulkrfli A.; Naing, Nyi Nyi (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2004)
In recent years, there has been concern that non-smokers may also be at risk from secondhand smoke exposure, especially children. This study was done to determine the prevalence of secondhand smoke exposure at home and the association between secondhand smoke exposure and respiratory symptoms among primary schoolchildren in Kota Bharu, Kelantan. This was a comparative cross-sectional study involving children, aged 10-12 years. A structured questionnaire was used to obtain the information on sociodemographic, respiratory symptoms and smokers in the house. A random sample of 10 from 95 primary schools in Kota Bharu was included. Six classes were randomly selected from each school, two classes each from each school year of primary 4-6. A total of 795 children completed the questionnaire during September 2003 till March 2004. 386 of children (48.6%) were boys and 409 children (51.4%) were girls. Most of the children were Malay (99.9%). A total of 442 (55.6%) children lived with at least 1 smoker in the house mainly from the smoking fathers. Significantly increased odds ratios due to secondhand smoke exposure were observed for most of the respiratory symptoms. The odds ratios (95% confidence interval) were 1.67 (1.18, 2.39) for cough in the morning, 1.59 (1.10, 2.30) for cough at night, 1.76 (1.16, 2.65) for cough most days for the previous 3 months, 1.57 (1.14, 2.17) for phlegm in the morning, 1.49 (1.08, 2.07) for phlegm during daytime or at night, 1.38 (1.03, 1.86) for nose problems in the morning, 1.40 (1.03, 1.90) for nose problems at night and 1.78 (1.14, 2.78) for throat problems at night, 1.55 (1.06, 2.26) for ever wheeze or diagnosed asthma by doctor, 1.57 (1.05, 2.36) for throat problems in the morning and 1.81 (1.15, 2.85) for throat problems during daytime. The odds ratios increased with increasing number of smokers at home for cough in the morning, cough most days for the previous 3 months, phlegm in the morning, ever wheeze or diagnosed asthma by doctor, throat problems in the morning, throat problems during daytime and throat problems at night. In view of the significant health risks posed to children by secondhand smoke, public health policies are needed to protect this vulnerable population. The aim of such policies is to ensure the right of every child to grow up in an environment free of tobacco smoke.